2020
DOI: 10.3389/fphar.2020.00273
|View full text |Cite
|
Sign up to set email alerts
|

Atractylenolide I Induces Apoptosis and Suppresses Glycolysis by Blocking the JAK2/STAT3 Signaling Pathway in Colorectal Cancer Cells

Abstract: Colorectal cancer (CRC) is the third most common cancer worldwide and is associated with a poor clinical outcome and survival. Therefore, the development of novel therapeutic agents for CRC is imperative. Atractylenolide I (AT-I) is a sesquiterpenoid lactone derivative of Rhizoma Atractylodis macrocephalae that exhibits diverse biological activities, including anti-cancer activities. However, the effects and potential mechanism of AT-I in CRC have yet to be fully elucidated. In this study, we aimed to examine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 54 publications
1
47
0
Order By: Relevance
“…In addition, it can enhance cell metabolism through HK2 upregulation. Previous studies have demonstrated that the IL-6/STAT3 and JAK2/STAT3 pathways can promote glycolysis, confirming the crucial role of STAT3 in AS and glycolysis (96,97). Therefore, STAT3 was proven to be an important factor in AS and glycolysis.…”
Section: Prediction and Analysis Of Targets Associated With Endothelimentioning
confidence: 71%
“…In addition, it can enhance cell metabolism through HK2 upregulation. Previous studies have demonstrated that the IL-6/STAT3 and JAK2/STAT3 pathways can promote glycolysis, confirming the crucial role of STAT3 in AS and glycolysis (96,97). Therefore, STAT3 was proven to be an important factor in AS and glycolysis.…”
Section: Prediction and Analysis Of Targets Associated With Endothelimentioning
confidence: 71%
“…AT-I is a novel TLR4-antagonizing agent (Liu et al, 2016), and it exerted anti-tumor effects on colorectal cancer, bladder cancer and melanoma (Fu et al, 2018;Guo et al, 2019;Li et al, 2020), then we investigated whether it could suppress tumorigenesis in Rat breast tissues were kept to detect TLR4/NF-κB pathway by western blot assay at the end of experiment. (G, H, I) TNF-α, IL-6 and IL-1β levels in rat breast tissues were analyzed by ELISA at the end of experiment.…”
Section: Discussionmentioning
confidence: 99%
“…AT-I is a novel TLR4-antagonizing agent [20], and it exerted anti-tumor effects on colorectal cancer, bladder cancer and melanoma [17][18][19], then we investigated whether it could suppress tumorigenesis in breast cancer via inhibiting TLR4/NF-κB pathway. Firstly, we found that AT-I could inhibit cell growth, proliferation, migration and invasion, and induce apoptosis in breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Rhizoma Atractylodis Macrocephalae, one of the traditional Chinese crude materials, had signi cant gastrointestinal tract protective, neuroprotective and immunomodulatory activities [13], and numerous lines of evidence showed that it also exerted anti-tumor, anti-in ammatory and antioxidant effects [13,14]. Atractylenolide I (AT-I), the major bioactive component from Rhizoma Atractylodes Macrocephalae, also had multiple therapeutic activities including anti-in ammatory [15,16] and anti-tumor effects [17][18][19]. Speci cally, AT-I could ameliorate LPS-induced lung damages in mouse model [15], and suppressed LPS-induced NO release and diminished pro-in ammatory cytokines levels in BV-2 cells [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation